Identifikasi Potensi dan Kelayakan Objek Daya Tarik Wisata Alam (ODTWA) Blok Hutan Kambata Wundut Taman Nasional Manupeu Tanadaru dan Laiwangi Wanggameti (Matalawa) - Umbu Yiama Selitara; Junaedin Wadu; Muhamad Indra Saputra Asnawi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to identify potential natural tourist attraction objects and assess the feasibility of natural tourist attraction objects (ODWA) in the Kambata Wundut Forest Block. Data collection in this research was carried out by direct observation and using documentation media and structured interviews using questionnaires. The samples in this research are the local community, visitors and people who have an interest in developing ODTWA in the Kambata Wundut Forest Block area. The sampling method used in this research is accidental sampling used for area managers and surrounding communities and quota sampling used for tourists. The data analysis method used to identify potential ODTWA uses descriptive analysis and to determine the level of feasibility of each assessment criteria consisting of: tourist attraction, condition of the surrounding area, management and services, accessibility, accommodation, facilities and infrastructure using the Regional Analysis Guidelines Operations of ADO-ODTWA Natural Tourism Objects and Attractions Director General of PHKA (2003). The research results show that the potential tourist attraction objects (ODTWA) of Kambata Wundut are: Kanabu Wulang cave, Bird Waching, cultural attractions (Marapu religious ceremonies), Kambata Wundut river and orchid plants. The feasibility potential index category in the Kambata Wundut Forest Block on the variables of tourist attraction, condition of the surrounding area, management and services, accessibility, and facilities and infrastructure is suitable for development, however, the accommodation criteria are not yet suitable for development due to the lack of available accommodation within the area. the lowest radius is >10km at that location. The results of the variable recapitulation using ADO-ODTWA showed a score of 76%, indicating that the area is suitable for development.